2021
DOI: 10.3325/cmj.2021.62.338
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adjunctive lidocaine-based scalp block and laryngotracheal local anesthesia vs general anesthesia only on plasma and cerebrospinal fluid pro-inflammatory cytokine concentrations in patients with cerebral aneurysm: a randomized controlled trial

Abstract: Aim To compare the effect of adjunctive lidocaine-based scalp block and laryngotracheal local anesthesia vs general anesthesia only on pro-inflammatory cytokine concentrations in patients with non-ruptured brain aneurysms undergoing elective open surgery. Methods This parallel, randomized, controlled, open-label trial was conducted at Clinical Hospital Center Zagreb between March 2019 and March 2020. At the beginning of anesthesia, lidocaine group received 40 mg of 2% l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Of the 502 records acquired from systematic search of the three databases (Figure 1), 12 were excluded for failing to meet the inclusion criteria. Finally, 12 RCTs involving 626 participants were included in the current meta‐analysis 19–30 . The characteristics of the included trials are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 502 records acquired from systematic search of the three databases (Figure 1), 12 were excluded for failing to meet the inclusion criteria. Finally, 12 RCTs involving 626 participants were included in the current meta‐analysis 19–30 . The characteristics of the included trials are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of the participants varied between 21 and 58 years. Eight trials included a placebo control group by conducting SB with saline (with or without epinephrine), 20–22,24,26–28,30 while SB was compared with IV remifentanil or no SB in the remaining four trials 19,23,25,29 . In three RCTs, SB was performed following completion of operation and skin closure, 20,24,26 whereas SB was administered before skin incision and craniotomy in the other nine trials 19,21–23,25,27–30 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations